Influence of Ease of Use, Service Features, and Promotion on the Intensity of DANA E-Wallet Usage (A Study on Students of Universitas Merdeka Madiun) - Rizaldy Dafa Efendi; Tatik Mulyati; Ahadiati Rohmatiah (International Journal of Business and Quality Research, 2026)
The rapid advancement of financial technology has revolutionized transaction methods from cash to cashless systems, with digital wallets like DANA becoming highly integrated into the daily routines of college students. This study aims to analyze the influence of ease of use, service features, and promotion on the intensity of DANA e-wallet usage among students of Universitas Merdeka Madiun. A quantitative causal explanatory research design was adopted. A purposive and stratified random sampling technique was used to select 170 active student respondents from a total population of 1,070 active students. Data were collected using structured questionnaires and analyzed using multiple linear regression analysis. The results demonstrated that ease of use, service features, and promotion simultaneously and positively predict the intensity of DANA e-wallet usage, F (3, 166) = 54.40, p < 0.001, explaining 48.7 percent of the variance (Adjusted R Square = 0.487). Partially, ease of use (t = 6.837, p < 0.001), service features (t = 6.524, p < 0.001), and promotion (t = 8.436, p < 0.001) each have a positive and significant effect on the intensity of usage, with promotion acting as the most dominant determinant. The study concludes that ease of use, service features, and promotion significantly contribute to shaping the intensity of e-wallet usage among students. The study recommends that e-wallet providers simplify transaction processes, innovate service features, and maintain attractive promotional programs to systematically enhance user engagement.